Investigation of synthesis methods of ZIF-8 membranes for CO2/CH4 separation - Mushtaq, Qasim M. (2022)
Although there has been a rapid expansion into renewable energies such as (bio)methane, hydrogen, solar PV and wind power, fossil fuels still account for approximately 80% of the total primary energy demand. Methane, whether produced via anaerobic digestion or taken from gas wells, is one of the cleanest of all fossil-derived fuels. However, the contaminant, CO2, creates challenges with production, e.g. pipeline corrosion where CO2 makes the stream acidic in the presence of water increasing operational costs. Membranes are a preferred method for separating gas mixtures since they are up to 50% more energy-efficient than conventional separation technologies e.g., absorption and distillation. The technology can be retrofitted to existing unit operations since membranes are very simple, compact, and easy to operate and control. However, commercially, amine absorption is the more dominant form of separation for the CO2/CH4 mixture due to amines high selectivity towards CO2. There are a few commercial polymeric membranes. However, the CO2 content (up to 75%) of the natural gas and the pressure of the separation (up to 50 bar) make polymer structure susceptible to plasticisation, which reduces the polymers lifespan and durability when in use, impeding selectivity leading to poor separation performance. For this reason, the research community has been actively investigated the alternative materials to polymers for membranes. An alternative to polymers is the hybrid structure of metal organic frameworks (MOFs), which are metal centres connected by organic linkers forming 'net' like structures. An advantage of MOFs is the tailorability of their structure, by changing the metal centre or organic linker, an infinite combination of structures can be developed and created for the designated gas mixture and processing condition. Another key advantage is their large surface to volume ratios, more than 6000 m2/g. ZIF-8 belongs to the zeolitic imidazolate frameworks (ZIFs) family, a subclass of MOFs with similar topology to the inorganic structure zeolite. ZIF-8 is of interest because of its high surface to volume ratio, chemical and thermal stability, hydrophobic nature, and ideal pore structure to exclude CH4 and natural affinity to CO2. However, there are challenges with synthesising continuous and dense ZIF-8 membranes onto substrates. For example, literature reiterates the difficulty with repeatability and reproducibility when growing the films onto substrates to form membranes. Production costs and scalability are issues too. This thesis explored the heterogeneous growth of ZIF-8 membranes onto tubular alumina substrates in batch systems using microwave and conventional heating, and deposition of MOFs onto flat substrates using spray coating. The batch systems investigated the role of precursor concentrations and ratios, conjugate base, and synthesis time on the heterogenous growth of ZIF-8 under their respective heating mechanisms. The batch systems also investigated the same parameters with the precursors isolated. The dynamic cold spray coating chapter studied the efficient deposition of MOFs onto flat substrates by optimising the atomisation of the slurry. Characterisation of the samples were conducted using X-ray diffraction to determine the formation and the crystallinity of the structures. Scanning electron microscopy was used to investigate the morphology, membrane thickness and surface coverage. The batch production results under conventional heating support other researchers' findings on the difficulty of achieving heterogeneous growth of ZIF-8 onto substrates since ZIF-8 is a predominantly homogenous nucleation process and some form of surface modification is needed to promote growth onto the substrate, particularly tubular substrates. The difficulty with tubular substrates is the low mass transfer efficiency inside the tubular substrate’s lumen. The results also showed how the synthesis conditions controlled the level of growth onto the substrate with low precursor concentrations delivering a weaker level of continuity of film growth onto the substrate, smaller linker/metal ratios forming larger crystals and thicker membranes, and longer synthesis times delivering more evolved crystals whilst no increase in the level of continuity of film growth. The novel metal-linker isolation work studied the formation of ZIF-8 by analysing the reaction and diffusion effects at the substrate's surface. The work emphasises the homogenous nature of ZIF-8, the work also suggested that the respective precursor location can control the crystal morphology and size (inside or outside of substrate), even when at the same linker/metal ratio. The synthesis of ZIF-8 onto tubular substrates under microwave heating showed how volumetric heating affects heterogenous growth since the microwave system achieved crystal growth on the tubular substrate in a 1 hour synthesis. A more robust level of heterogenous growth of ZIF-8 was also achieved in the microwave system by increasing solvent volume to 16 ml from 4 ml to accommodate the microwave chemistry. The cold spray coating enhanced particle attachment by optimising the mechanical parameters when designing the atomiser for the coating of MOFs onto substrates. The result indicates that the optimum mechanical conditions for pressure, stand of distance (SOD), the number of passes and angle of injection are 2 bar, 300 mm, two passes, and 90 °, respectively. The novel design of the atomiser can be applied to temperature-sensitive MOF/ZIF structures.